Health and functional advantages of cheese containing soy protein and soybean-derived casein - Messina, Mark; Messina, Virginia (Frontiers in Plant Science, 2024)
The global food system faces a challenge of sustainably producing enough food, and especially protein, to meet the needs of a growing global population. In developed countries, approximately 2/3 of protein comes from animal sources and 1/3 from plants. For an assortment of reasons, dietary recommendations call for populations in these countries to replace some of their animal protein with plant protein. Because it is difficult to substantially change dietary habits, increasing plant protein may require the creation of novel foods that meet the nutritional, orosensory, and functional attributes consumers desire. In contrast to plant-based milks, plant-based cheeses have not been widely embraced by consumers. The existing plant-based cheeses do not satisfactorily mimic dairy cheese as plant proteins are unable to replicate the functional properties of casein, which plays such a key role in cheese. One possible solution to overcome current constraints that is currently being explored, is to produce hybrid products containing soy protein and soybeanderived casein. Producing soybean-derived casein is possible by utilizing traditional genetic engineering tools, like Agrobacterium-mediated plant transformation, to express genes in soybeans that produce casein. If a cheese containing soy protein and soybean-derived casein satisfactorily mimics dairy, it presents an opportunity for increasing plant protein intake since US dairy cheese consumption has been steadily increasing. Soybeans are an excellent choice of crop for producing casein because soybeans are widely available and play a large role in the US and world food supply. Additionally, because a casein-producing soybean offers soybean farmers the opportunity to grow a value-added crop, expectations are that it will be welcomed by the agricultural community. Thus, there are benefits to both the consumer and farmer.